Calificación de la cadena de frío durante el proceso de embalaje, transporte y distribución de una distribuidora farmacéutica, 2017 - Marcos Rodríguez, Jesi Fiorela (2019)
The present study is aimed at determining the rating of the cold chain during the process of packaging, transport and distribution of a pharmaceutical distributor. The investigation begins with selection of the simulation product. Then, the equipment to be used was tested and the Gel packs at -10 ° C were adjusted. Subsequently, two packaging classes A and B were designed for the container of thermal insulation type 1 (42cm x 32cm x 26cm), also C and D for type 2 (24cm x 29cm x 24.5cm). Finally, the qualification tests of the packing, transport and distribution process are carried out, where the temperature is monitored from the point of origin to the point of final destination. It is concluded that the process of packaging, transport and distribution complies with keeping the cold chain within the established range